2021
DOI: 10.1111/clr.13702
|View full text |Cite
|
Sign up to set email alerts
|

Implantoplasty: Carbide burs vs diamond sonic tips. An in vitro study

Abstract: Objectives Implantoplasty (IP) is a treatment option for peri‐implantitis. Mechanical concerns were raised on fracture resistance of implants subjected to this procedure. This study aimed to compare two methods of IP in terms of implant wear and fracture resistance, and of surface topography. Material and methods Eighteen cylindrical screw‐shaped dental implants (4 mm diameter, 13 mm length) with an external hexagonal connection were used. IP was performed on the first 6‐mm implant surface with a sequence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…However, there is some indication that internal hexagon connection may be the weakest abutment connection design. Interestingly, the other studies which used implants with external hexagon connection showed that implantoplasty did not affect fracture resistance (Costa-Berenguer et al, 2018;Leitao-Almeida et al, 2020;Leitão-Almeida et al, 2021;Sivolella et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is some indication that internal hexagon connection may be the weakest abutment connection design. Interestingly, the other studies which used implants with external hexagon connection showed that implantoplasty did not affect fracture resistance (Costa-Berenguer et al, 2018;Leitao-Almeida et al, 2020;Leitão-Almeida et al, 2021;Sivolella et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale given was that the test implants fractured at the abutment screw, which did not influence the implant body. Out of the six studies which involved regular diameter implants, three studies (Chan et al, 2013;Costa-Berenguer et al, 2018;Sivolella et al, 2021) concluded that implantoplasty did not affect the fracture resistance while the other three (Bertl et al, 2020;Gehrke et al, 2016;Jorio et al, 2021) found a significant decrease in fracture resistance after implantoplasty.…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…For accessible surface, implantoplasty can be performed using a high speed carbide bur with rigorous water cooling to further remove residual dental plaque and their associated debris and to convert a rough to a smoothened surface, allowing more effective plaque removal during maintenance phase by patients and treating clinicians (56,90,91). Various adjunctive therapeutic modalities in addition to non-surgical therapy were reported utilizing systemic antibiotics, locally delivered antimicrobial, laser, photodynamic therapy, and air polishing; however clinicians should carefully utilize these modalities considering a limited availability of evidence in the literature (74,85,87,88,(92)(93)(94).…”
Section: Non-surgical Peri-implant Therapymentioning
confidence: 99%